A concise approach for the synthesis of 3-iodoindoles and 3-iodobenzo[b]furans via Ph3P-catalyzed iodocyclization. Issue 43 (28th October 2015) - Li, Yin-Long; Li, Jian; Yu, Sheng-Nan; Wang, Ji-Bo; Yu, Yan-Min; Deng, Jun
Abstract: A variety of 3-iodoindole and 3-iodobenzo[ b ]furan derivatives were conveniently prepared from the corresponding 2-alkynylanilines and 2-alkynylphenols through Ph3 P-catalyzed iodocyclization in the presence of N -iodosuccinimide (NIS). This protocol provides a rapid access to 3-iodoindoles and 3-iodobenzo[ b ]furans in good to excellent yields under mild conditions. Graphical abstract: